Integrating Eco-Sufi Values into Environmental Education through the Adiwiyata Madrasah Program - Bahtiar, Auliak; Rizal, Syaiful; Roisyah, Hannani; Angkananon, Chumphon (Journal of Islamic Education Research, 2025)
Accelerating climate change and biodiversity loss reveal a profound moral–spiritual rupture that requires faith based educational responses. Anchored in a descriptive qualitative design, we spent one semester observing learning routines, interviewing five key informants, and analysing curricular documents at MTs Unggulan Al Qodiri Jember; credibility was ensured through source?method triangulation and member checks. The Adiwiyata Madrasah programme operationalises Eco Sufi virtues (tazkiyatun nafs, mujahadah, zuhud, tawakkal, and mahabbah) via Clean Friday reflections, a student?led waste?bank, and the Best Class eco competition. Supportive policies, enthusiastic students, and OSIM leadership accelerate adoption, whereas limited teacher literacy and scarce learning resources constrain systematic infusion. Embedding Eco Sufi values heightens students’ ecological concern, discipline, and social empathy, showing that spiritually grounded environmental education can reinforce national sustainability agendas while fostering holistic character in Islamic schools. Scaling this model requires targeted teacher training, richer instructional media, and cross institutional robust knowledge exchange initiatives.